2019
DOI: 10.3389/fphar.2019.00505
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Pharmacokinetics and Safety of Ibuprofen and Its Enantiomers in the Conventional Pig as Potential Pediatric Animal Model

Abstract: Pediatric drug development, especially in disease areas that only affect children, can be stimulated by using juvenile animal models not only for general safety studies, but also to gain knowledge on the pharmacokinetic and pharmacodynamic properties of the drug. Recently, the conventional growing piglet has been suggested as juvenile animal model. However, more studies with different classes of drugs are warranted to make a thorough evaluation whether the juvenile pig might be a suitable preclinical animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
(58 reference statements)
0
15
0
Order By: Relevance
“…It should be noted, however, that the lower AUC ratio for 2OH-IBU and COOH-IBU in the 6- to 7-month-old pigs could also be attributed to the much higher AUC of IBU. This higher AUC might be a consequence of the lower V d in the 6- to 7-month-old pigs compared to younger pigs, as has been demonstrated by Millecam et al, (2019). As can be seen from Table 1 , the C 0 of IBU after IV administration was indeed significantly higher compared to the other age categories, pointing towards a lower V d .…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…It should be noted, however, that the lower AUC ratio for 2OH-IBU and COOH-IBU in the 6- to 7-month-old pigs could also be attributed to the much higher AUC of IBU. This higher AUC might be a consequence of the lower V d in the 6- to 7-month-old pigs compared to younger pigs, as has been demonstrated by Millecam et al, (2019). As can be seen from Table 1 , the C 0 of IBU after IV administration was indeed significantly higher compared to the other age categories, pointing towards a lower V d .…”
Section: Discussionmentioning
confidence: 51%
“…The total IBU concentrations were determined as the sum of R- and S-IBU using a validated ultra performance liquid chromatography with an ultraviolet detector (UPLC-UV) method according to Millecam et al (2019). IBU metabolites were quantified using an in-house developed and validated ultra-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) method.…”
Section: Methodsmentioning
confidence: 99%
“…Despite this limited data we were able to confirm a higher CL R compared to CL S , as also observed in other preterm neonates and older populations (Figure 2). 10,11,34–36 The limited data available can also explain the lack of identification of chiral inversion of R‐ to S‐ibuprofen, as identified in piglets and well described in adults 7,13 . However, the varying fractions of R‐ibuprofen dose to be inverted identified by Gregoire et al (17 and 61%) already suggested difficulties with identifying this inversion in preterm neonates.…”
Section: Discussionmentioning
confidence: 99%
“…Kearns & Reed report that Phase I hepatic transformation (eg, CYP2C) progressively increases to near adult values by 6 months of age . Further support for a maturation profile that is rapid comes from infant pigs (1 week, 4 weeks, 8 weeks, 6 months) that were used to investigate ibuprofen developmental pharmacokinetics . Peak clearance estimates (5.6 mL/min/kg) were in piglets aged 8 weeks.…”
Section: Discussionmentioning
confidence: 99%